MENANAMKAN PENDIDIKAN KARAKTER ANAK USIA DINI DI MASA GOLDEN AGE SESUAI Q.S LUKMAN : 13 – 19 - Musayyadah, Dewi Pusparini, Rizal Muhammad Farasyi, Norma Gupita, (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2019)
As we know, Early Childhood (AUD) is in the golden age in the growth and development of humans both physically, emotionally, socially, and spiritually, so that to get the optimal and optimal results, character education must be starting from AUD. In the Qur'an it is very clear, the Qur'an as a way of life for Muslims has taught and illustrated how character education must be taught to children as the main and fundamental provision in living life in the world. To be able to understand how character education is, then we can use the Bayani method which includes: identification of the Qur'an which will be studied, identification of the related texts, and understanding texts in a textual and contextual manner. . By using the Bayani method, character education according to Surah Lukman: 13-19, as follows: train and familiarize loyalty, respect, gratitude, critical, curiosity, friendliness, responsibility, discipline, courage, patience, caring for others, not arrogant, modest life, and manners. If character education according to Q.S Lukman: 13-19 is carried out by parents in educating their children, as Lukman told his children then moral decadence can be minimized and Indonesian people will achieve glory and glory.